2020
DOI: 10.5194/cp-16-1715-2020
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian framework for emergent constraints: case studies of climate sensitivity with PMIP

Abstract: Abstract. In this paper we introduce a Bayesian framework, which is explicit about prior assumptions, for using model ensembles and observations together to constrain future climate change. The emergent constraint approach has seen broad application in recent years, including studies constraining the equilibrium climate sensitivity (ECS) using the Last Glacial Maximum (LGM) and the mid-Pliocene Warm Period (mPWP). Most of these studies were based on ordinary least squares (OLS) fits between a variable of the c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 58 publications
0
37
0
Order By: Relevance
“…The temperature anomaly of LGM relative to PI over the tropics is negative and there is general quantitative agreement between the anomaly derived from the model and that from proxy data (Bartlein et al, 2011;MARGO project members et al, 2009). This could be useful in constraining future projections, given that Annan and Hargreaves (2006) and Renoult et al (2020) revealed the correlation between tropical cooling at LGM and ECS. It has been pointed out in Stocker et al (2013) Fifth Assessment Report that the cooling over Greenland during the LGM relative to PI is underestimated in the models.…”
Section: Outlook and Conclusionmentioning
confidence: 53%
See 2 more Smart Citations
“…The temperature anomaly of LGM relative to PI over the tropics is negative and there is general quantitative agreement between the anomaly derived from the model and that from proxy data (Bartlein et al, 2011;MARGO project members et al, 2009). This could be useful in constraining future projections, given that Annan and Hargreaves (2006) and Renoult et al (2020) revealed the correlation between tropical cooling at LGM and ECS. It has been pointed out in Stocker et al (2013) Fifth Assessment Report that the cooling over Greenland during the LGM relative to PI is underestimated in the models.…”
Section: Outlook and Conclusionmentioning
confidence: 53%
“…As LGM cooling relative to the pre-industrial (PI) experiment over the tropics is at a comparable level to equilibrium climate sensitivity (ECS), LGM modeling can provide useful information to constrain climate sensitivity for projections of future climate (Annan and Hargreaves, 2006;Renoult et al, 2020). Intercomparison studies of proxy-based reconstructions of climate variables and model output continue to be conducted (Braconnot et al, 2007;Bartlein et al, 2011;Kageyama et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For all emergent constraints, we use the historical simulations of CMIP5 and CMIP6 in order to ensure maximum agreement with the observational data. If necessary, the historical simulation of CMIP5 is extended after its final year 2005 with data from the RCP8.5 scenario (Riahi et al, 2011). Note that we only use data through 2014, during which time all RCP scenarios behave similarly and the choice of the scenario is not expected to affect results considerably.…”
Section: Calculation Of Emergent Constraints On Ecsmentioning
confidence: 99%
“…Similar to many other emergent constraint studies, we use an ordinary least-squares linear regression model for each emergent constraint. However, in some cases this might not be appropriate, e.g., when we expect nonlinear behavior or when physical constraints can be used to derive further constraints for the regression model like a zero intercept (Annan et al, 2020; Jimenez-de-la-Cuesta and Renoult et al, 2020).…”
Section: Calculation Of Emergent Constraints On Ecsmentioning
confidence: 99%